Spatial analysis of metabolic syndrome among healthcare workers in a suburban area - Apriningsih Apriningsih; Ayu Arini Firlia; Meiyetriani Eflita (BIO Web of Conferences)
This study aims to investigate the prevalence and spatial distribution of metabolic syndrome (MetS), obesity, hypertension, and high cholesterol levels among health workers in Depok City. 614 respondents were surveyed, with most female (75.1%) and aged 25-34 (44.3%). The study found high rates of high blood pressure (33.2%), high cholesterol levels (30.3%), and metabolic syndrome (40.7%), with 47.6% classified as obese. Spatial analysis revealed significant correlations between metabolic syndrome and obesity (p<0.05). Obesity plays a substantial effect in metabolic syndrome prevalence. More study is needed to investigate obesity-targeted interventions to reduce metabolic syndrome prevalence.